Gellan gum-and pectin-magnetic graphene oxide nanocarriers loaded with cinnamaldehyde for mosquito larvae control - Wong, Siew Tin Susana (Penerbit Universiti Teknologi Malaysia, 2024)
Magnetic nanoparticles have evolved over the last few decades as nanocarriers in drug delivery systems for hydrophobic drugs. Here, novel gellan gum magnetic graphene oxide (GG-GO-Fe3O4) and pectin magnetic graphene oxide (PEC-GO-Fe3O4) nanocomposites were prepared to carry cinnamaldehyde to control Aedes aegypti larvae. Fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM) and scanning transmission electron microscopy (STEM) were employed to investigate the physicochemical characteristics of the nanocomposites. Entrapment efficiencies and loading capacities of nanocomposites on cinnamaldehyde were examined using ultraviolet-visible analysis. The successful cinnamaldehyde loading was confirmed by C-C and C-O stretches in the FTIR spectra. Results of in vitro release study showed the capabilities of GG-GO-Fe3O4 as a drug carrier system, extending the cinnamaldehyde release period for 36 h, and the release profiles for both nanocomposites fit the Korsmeyer-Peppas kinetic model with correlation coefficient (R2) values of over 0.9809. The cinnamaldehyde-loaded GG-GO-Fe3O4 nanocomposites induced 68% mortality after 72 h of exposure, with LC50 values ranging from 2.0488 and 15.9121 mg/L. The conjugation of GO-Fe3O4 with biopolymers improved the water solubility of cinnamaldehyde by 36.41 to 62.83 times vs. free cinnamaldehyde in water (1.42 mg/mL). Overall, these results are beneficial for researchers dealing with mosquito control and prevention.